TRANSPARANSI LAPORAN KEUANGAN: IMPLIKASI PENERAPAN PSAK 68 (Fair Value Accounting) KAJIAN LITERATUR PERSPEKTIF INVESTOR - Subari Subari; Eka Julianti Efris Saputri; Aditya Pradana; Liona Efrina (Komunitas Manajemen Kompetitif, 2026)
The application of fair value in financial reporting through PSAK 68 aims to increase the transparency and relevance of financial information for investors. This study examines the implications of implementing PSAK 68 on financial statement transparency based on a literature review. The method used is a literature review, reviewing relevant journals, books, and academic sources. The results of the study indicate that PSAK 68 can increase transparency by presenting values that reflect market conditions and requiring disclosure of valuation techniques and assumptions. However, the use of Level 2 and Level 3 inputs in measuring fair value has the potential to introduce subjectivity, which can reduce the reliability of the information. From an investor perspective, the quality of fair value disclosure significantly influences trust and investment decision-making. Therefore, the implementation of PSAK 68 requires clear and accountable disclosures to optimally achieve the benefits of transparency